1986
DOI: 10.1128/jb.166.1.224-229.1986
|View full text |Cite
|
Sign up to set email alerts
|

Role of glutamine synthetase adenylylation in the self-protection of Pseudomonas syringae subsp. "tabaci" from its toxin, tabtoxinine-beta-lactam

Abstract: Selected pathovars of Pseudomonas syringae produce an extracellular phytotoxin, tabtoxinine-p-lactam, that irreversibly inhibits its known physiological target, glutamine synthetase (GS). Pseudomonas syringae subsp. "tabaci" retains significant amounts of glutamine synthetase activity during toxin production in culture. As part of our investigation of the self-protection mechanism(s) used by these pathovars, we have determined that GS becomes adenylylated after toxin production is initiated and that the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…GS is irreversibly inactivated by T,L in vitro (6,7,19). We report data showing that in vivo GS activity is not affected by the presence of TPL in liquid culture of a Tox+ strain.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…GS is irreversibly inactivated by T,L in vitro (6,7,19). We report data showing that in vivo GS activity is not affected by the presence of TPL in liquid culture of a Tox+ strain.…”
mentioning
confidence: 76%
“…We have shown that adenylylation of GS offers partial protection for GS against T,3L by slowing the rate of inactivation (6). Adenylylation of GS is correlated with the accumulation of serine that accompanies the enzymatic hydrolysis of tabtoxin to release serine and T,L (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It usually brings about changes in the reactivity of the enzyme, 35) and several Pseudomonas GS are known to be adenylylated in response to culture conditions. 23,29) …”
Section: Resultsmentioning
confidence: 99%
“…In the case of whole cells as an enzyme preparation, cetyltrimethylammonium bromide (CTAB, 0.1 mg/ml) was added to the reaction mixture. 28,29) (3) -Glutamyl-transferring reaction (GT-reaction): One unit of the activity (GTactivity) was defined as the amount of enzyme forming 1 mmol of -glutamylhydroxamate per min.…”
mentioning
confidence: 99%